Evaluation of the biocidal effects of Brassica seed meal on Armillaria mellea. (29th June 2015) - Baldi, E.; Toselli, M.; Malaguti, L.; Lazzeri, L.
Abstract The antifungal properties of isothiocyanates released from the hydrolysis of the glucosinolate sinigrin were assessed on an Armillaria mellea strain in Petri dishes. The fumigation with sinigrin at 100 µM showed a fungicidal effect, while lower rates determined a temporary fungistatic effect. The application of increasing rates of solid and liquid biofumigant formulations on A. mellea inoculated potted peach plants showed an increase of soil nitrate concentration, basal respiration, microbial biomass, leaf nitrogen and chlorophyll concentration. These effects indicated a stimulating effect of Brassicaceae derivatives on soil biological activity and plant growth. The application of a rate of meal higher than 6.42 g kg−1 soil caused a stunted growth and the death of some plants showing a clear phytotoxic effect of the treatments. The inhibition of A. mellea growth observed in in vitro trials was not evidenced in in vivo experiments due to the lack of infection symptoms in experimentally inoculated potted trees.